EFL STUDENTS’ ENGAGEMENT DURING INTERACTIVE READ ALOUD - Fadillah Sandy; Laksananing Mukti (IAIN Syekh Nurjati Cirebon, 2020)
This study explores EFL students’ engagement during interactive read-aloud activity. Students’ engagement was observed in two meetings (Mean= 70 minutes). The subject of this research was the 10th grade of high school students. The data was taken from the teacher’s field notes and the students’ essay (n= 32). The teacher’s field notes were used as a tool to see how interactive read aloud was applied; while students’ essays were used to gather the students’ writing performance and language functions. The result shows that in behavioural engagement the students were very much engaged during the classroom activity. As in cognitive engagement, it could be seen that the students used to mix languages in delivering their idea in spoken, while in writing, most of the students had excellent ability to elaborate their idea. Students showed their affective engagement through their excitement and eagerness while listening and discussing story book during interactive read-aloud.